The effects of Bifidobacterium animalis QC08 on reducing uric acid level and providing renal protection in mice with hyperuricemia - Mao, Huijia; Fan, Yang; Tan, Fang; Long, Xingyao (Frontiers in Microbiology, 2025)
ObjectiveThe present study aimed to investigate the uric acid-lowering effects of Bifidobacterium animalis QC08 and explore its underlying mechanisms.MethodsHyperuricemia (HUA) model in mice was established using potassium oxonate (250 mg/kg) and yeast extract (15 g/kg). The serum levels of uric acid (UA), blood urea nitrogen (BUN), creatinine (Cr), and liver xanthine oxidase (XO) were measured in four groups, including normal group, control group, allopurinol group (5 mg/kg), and Bifidobacterium animalis QC08 group (1010 CFU/kg) using enzyme colorimetry. Additionally, serum tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) levels were assessed using enzyme-linked immunosorbent assay (ELISA). Pathological changes in renal tissue were examined through hematoxylin–eosin (HE) staining.ResultsIn vivo experimental results indicated that compared with the normal group, the serum UA, Cr, and BUN levels, as well as the levels of inflammatory factors (TNF-α and IL-1β), and the activities of hepatic xanthine oxidase (XOD) and adenosine deaminase (ADA) were significantly elevated in the control group (p < 0.05). The expression levels of uric acid transport-related genes (UAT, ABCG2, and OAT1) in kidney tissue were significantly downregulated (p < 0.05), and evident kidney damage was found. In contrast, compared with the control group, the Bifidobacterium animalis QC08 group exhibited a significant decrease in serum UA, BUN, Cr, TNF-α, and IL-6 levels, along with reduced hepatic XOD and ADA activities (p < 0.05). Additionally, Bifidobacterium animalis QC08 was found to regulate the mRNA transcription of renal uric acid transporters, leading to significantly upregulation of the expression levels of UAT, ABCG2, and OAT1 genes (p < 0.05).ConclusionBifidobacterium animalis QC08 demonstrates certain uric acid-lowering, anti-inflammatory, and renal protective effects, which are associated with the inhibition of XOD activity and the modulation of the expression levels of uric acid transporter genes (UAT, ABCG2, and OAT1).